2004
DOI: 10.1007/s00429-004-0380-7
|View full text |Cite
|
Sign up to set email alerts
|

Opposing regulation of cell proliferation by retinoic acid and the serotonin 2B receptor in the mouse frontonasal mass

Abstract: Development of the frontonasal mass (FNM), branchial arches, heart, and limbs depends on neural crest-mediated epithelial-mesenchymal (E-M) interactions. Teratogenesis by retinoic acid (RA) or blockade of serotonergic (5-HT) signaling by the pan-5-HT(2) receptor antagonist, ritanserin, perturbs development of these embryonic structures. In both cases, resulting phenotypes include forebrain and olfactory placode anomalies, malformations of the face, eye and lens, as well as posterior neural tube and cardiac def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In previous work, we have demonstrated that signaling through 5-HT2B is also involved in eye morphogenesis in Xenopus embryos (De Lucchini et al, 2005;Reisoli et al, 2008). Expression of 5-HT2B in the craniofacial region of mice, as well as the potent teratogenic activity of its antagonists in cultured mouse embryos, suggest that this receptor might play a role in craniofacial development (Choi et al, 1997;Bhasin et al, 2004b). In spite of this evidence, a direct role for 5-HT2B in craniofacial morphogenesis has still to be defined.…”
Section: Introductionmentioning
confidence: 96%
“…In previous work, we have demonstrated that signaling through 5-HT2B is also involved in eye morphogenesis in Xenopus embryos (De Lucchini et al, 2005;Reisoli et al, 2008). Expression of 5-HT2B in the craniofacial region of mice, as well as the potent teratogenic activity of its antagonists in cultured mouse embryos, suggest that this receptor might play a role in craniofacial development (Choi et al, 1997;Bhasin et al, 2004b). In spite of this evidence, a direct role for 5-HT2B in craniofacial morphogenesis has still to be defined.…”
Section: Introductionmentioning
confidence: 96%
“…These sites appear to protect the underlying mesenchyme from exposure to inappropriate levels of 5-HT, as indicated by patterns of cell death and malformations, caused by exposure of cultured mouse embryos to selective 5-HT reuptake inhibitors (SSRIs), like fl uoxetine (Prozac) and sertraline (Zoloft) [Shuey et al, 1992]. As shown in a variety of in vitro models, 5-HT acts as a dose-dependent growth regulatory signal for craniofacial cells, regulating neural crest migration [Moiseiwitsch and Lauder, 1995], mesenchymal cell proliferation [Bhasin et al, 2004b;Buznikov et al, 2001;Nebigil et al, 2000], tooth germ development [Moiseiwitsch and Lauder, 1996], and expression of growth factors and extracellular matrix molecules, including those of the cartilage matrix [Lambert and Lauder, 1999;Lambert et al, 2001;Moiseiwitsch and Lauder, 1997;Moiseiwitsch et al, 1998]. Serotonin carries out these diverse developmental functions by activating different 5-HT receptor subtypes [Buznikov et al, 2001;Lambert et al, 2001], including 5-HT 2 receptors [Bhasin et al, 2004a, b;Lauder et al, 2000].…”
Section: Serotonergic Regulation Of Mouse Craniofacial Developmentmentioning
confidence: 99%
“…This prompted an investigation of embryonic expression patterns for 5-HT receptors and retinoid markers in the mouse embryo, which revealed common patterns for the 5-HT 2B receptor, RALDH2 and CRABP1 in the craniofacial region, limbs, and heart [Bhasin et al, 2004b]. In support of this hypothesis, it was found that 5-HT promoted cell proliferation, mediated by 5-HT 2B receptors in organotypic cultures of the frontonasal mass, whereas at-RA, inhibited proliferation [Bhasin et al, 2004b]. Similarly, in hindlimb micromass cultures, stimulation of 5-HT 2B receptors was found to promote chondrogenic differentiation, whereas at-RA inhibited this process [Bhasin et al, 2004a].…”
Section: Retinoic Acid (Ra) and 5-ht May Regulate Embryonic Developmementioning
confidence: 99%
“…Except for 5-HT3 receptors, which are ligand-gated ion channels, all belong to G protein-coupled receptors and among these, the 5-HT2 receptors class seems to be particularly important in mediating the effects of 5-HT on embryonic development. Blockade of serotonergic signaling by the pan-5-HT2 receptor antagonist ritanserin perturbs development of the heart, the face and eyes both in mice and Xenopus, suggesting a conservation of this signaling pathway across vertebrate evolution (Choi et al, 1997;Bhasin et al, 2004;De Lucchini et al, 2005). The 5-HT2B receptor has been shown to be an important regulator of the mouse cardiac morphogenesis since its genetic ablation leads to mouse embryonic and postnatal lethality due to abnormal heart development (Nebigil et al, 2000;Nebigil et al, 2001).…”
Section: Abstract: 5-ht2b Neural Crest Cell Eye Craniofacial Morpmentioning
confidence: 99%
“…However, developmental craniofacial defects in 5-HT2B knockout mouse embryos have not been reported, probably because the most penetrating phenotype of 5-HT2B mutant mice leads to early embryonic death in utero (Nebigil et al, 2000). A possible role of the 5-HT2B signaling in craniofacial morphogenesis was suspected due to the potent teratogenic activity of its antagonists in cultured mouse embryos (Choi et al, 1997;Bhasin et al, 2004). In spite of this evidence, the precise mechanisms of the 5-HT2B function in craniofacial morphogenesis awaited to be defined.…”
Section: -Ht2b Signaling and Craniofacial Morphogenesis/jaw Joint Fomentioning
confidence: 99%